2008
DOI: 10.1108/17471110810892857
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the responsiveness of companies: corporate social responsibility to stakeholders

Abstract: PurposeThe purpose of this paper is to highlight practical manifestations of CSR and limitations of company responsiveness following these realities.Design/methodology/approachEmpirical research into responsiveness of miners to Australian Indigenous communities, alongside exploration of corporate history and composition. A range of sources was utilised, including participant interviews and quantitative data. The paper begins by discussing the primacy of commercial interest in CSR, then gives an example of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Thus, good CSR or good 'corporate citizenship' involves "making sure that the programs [invested] in fit with [corporate] business, achieving real business-oriented goals, as well as societal ones, and engaging employees and customers" (GolinHarris, 2005). Therefore, CSR can be identified as being primarily a business strategy for the pursuit of profit maximization, or preventing loss of profits attributable to secondary stakeholder activism with the interests of employees, consumers and the environment as secondary goals (Trebeck, 2008;Whitehouse, 2006). However, such a business strategy often implies a tri-sector partnership of government, private enterprise and society for successful CSR practice (Koladkiewicz, 2009;Szczepanski et al, 2009;Eweje, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, good CSR or good 'corporate citizenship' involves "making sure that the programs [invested] in fit with [corporate] business, achieving real business-oriented goals, as well as societal ones, and engaging employees and customers" (GolinHarris, 2005). Therefore, CSR can be identified as being primarily a business strategy for the pursuit of profit maximization, or preventing loss of profits attributable to secondary stakeholder activism with the interests of employees, consumers and the environment as secondary goals (Trebeck, 2008;Whitehouse, 2006). However, such a business strategy often implies a tri-sector partnership of government, private enterprise and society for successful CSR practice (Koladkiewicz, 2009;Szczepanski et al, 2009;Eweje, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple researchers explored the notion that companies may have retracted their investment in CSR to protect their economic position in this uncertain time and found that this occurred with the cost of these activities being a major factor, which was the finding of other research as well (J. Nasi, S. Nasi, Phillips, & Zyglidopoulos, 1997;Trebeck, 2008, Giannarakis & Theotokas, 2011. However, Giannarakis and Theotokas (2011) also argued that CSR and its cost should not only be seen as a threat, but also a great opportunity.…”
Section: Financial Institutions and Csrmentioning
confidence: 92%
“…Within the broader context of corporate social responsibility (CSR) -which provides a platform for an organization to manage its obligations to shareholders who have obligations to other stakeholders (Anderson, & Bieniaszewska, 2005;Banerjee, 2008;Carroll, 1991;Dahlsrud, 2006;Maclagan, 1999), social license to operate is typically understood as an underlying driver of corporate social behaviour that is embedded in the overall corporate CSR strategy (Carroll, 1991;Lotila, 2010;Trebeck, 2008). The need for a social license is perhaps most explicitly demonstrated in discussions of the "triple bottom line" approach to CSR, where some researchers see a direct link between an organization's license to operate and an organization's ability to create tangible value beyond finances, most successfully demonstrated through various community investment efforts (Kaptein & Van Tulder, 2003;Prexl & Signitzer, 2008).…”
Section: Social License and Corporate Social Responsibilitymentioning
confidence: 99%